2013
DOI: 10.1556/aagr.61.2013.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous selection of yield and yield stability in chickpea genotypes using the GGE biplot technique

Abstract: GGE biplot analysis is an effective method, based on principal component analysis (PCA), to fully explore multi-environment trials (METs). It allows visual examination of the relationships among the test environments, genotypes and the genotype-byenvironment interactions (G×E interaction). The objective of this study was to explore the effect of genotype (G) and the genotype × environment interaction (GEI) on the grain yield of 20 chickpea genotypes under two different rainfed and irrigated environments for 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…The significant interaction differences of genotypes × environment implied that application of stability analysis for identifying widely and/or specifically adapted upland rice genotype (s) is essential. These results are in agreement with those of Balestre et al, [10], Farshadfar et al, [17] and Biswas et al, [18]. The significant GE interaction in this study suggests the possible existence of different mega-environments.…”
Section: Analysis Of Variance and Agronomic Performancesupporting
confidence: 94%
“…The significant interaction differences of genotypes × environment implied that application of stability analysis for identifying widely and/or specifically adapted upland rice genotype (s) is essential. These results are in agreement with those of Balestre et al, [10], Farshadfar et al, [17] and Biswas et al, [18]. The significant GE interaction in this study suggests the possible existence of different mega-environments.…”
Section: Analysis Of Variance and Agronomic Performancesupporting
confidence: 94%
“…The perpendicular lines are equality lines between adjacent genotypes on the polygon, which facilitate visual comparison of them. The equality lines divide the biplot into sectors, and the winning genotype for each sector is the one located on the respective vertex (Yan & Tinker, 2006;Farshadfar et al, 2011). In the biplot using the first two principal components, the variables disease severity, yield, and oil content were located on three different sectors (Figure 2), within the third and fourth concentric circles (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…4) was observed for SPS, except for the high response of genotype HR to all environments. Farshadfar et al (2012) and Farshadfar (2013) showed different values of variability and G × E interactions for 16 genotypes of bread wheat (Triticum aestivum L.) in six environments and for 20 genotypes of chickpea in eight environments for yield and yield components. …”
Section: G×e Interaction In Wheat−barley Addition Linesmentioning
confidence: 99%